Why private markets are the best capital allocators for energy transition investments - Grigsby, Owen, author; Hoag, Dana, advisor; Seidl, Andrew, committee member (Colorado State University. Libraries, 2025)
Globally, investment in renewable energy and related infrastructure must rise dramatically in coming years to achieve climate change mitigation goals. Conventional financing methods, particularly public markets investment and government support, show inherent flaws when it comes to funding the renewable energy transition. Swings in political and public sentiment over climate change create policy uncertainty and drive volatility in public markets. Since private markets generally use a partnership model that is both inherently long-term focused and gives low liquidity to investors, they can serve the needs of these investments best. While sufficient capital is not yet being directed towards the renewable energy transition, the unique abilities of private markets investment can step in to fill this gap going forward. As such, policymakers, business leaders, and investors should bear this in mind when considering the renewable energy finance situation.
Keywords: economics; finance; climate change